Design change propagation to support assembly systems in digital twins - Vogt, Maximilian Gordian (Nanyang Technological University, 2022)
In recent years mass customization has become popular with a large number of products. This increases volatility in product design, which amplifies the complexity of production as well. One of the areas which are most directly affected by design changes is assembly lines. Industry 4.0 enables manufacturers to tackle these challenges with technical innovations such as the Digital Twin. Used as a virtual model of a physical system it can support engineers to estimate the impact of changing production environments and decision making. This dissertation provides a framework that connects product design and an assembly system in preparation for the implementation into Digital Twins. A literature review on product architecture, Design for Manufacturing and Assembly, and production is performed. Assessment models for each of these topics are analyzed and compared. Due to the inaccuracy of existing models in low volume productions, an adjustable manual assembly time estimation method with a broader range of factors is developed. The proposed estimation method is then integrated into the framework to gauge the impact of design changes on assembly lines. This framework consists of assembly time estimation, line rebalancing, and reconfiguration as well as assembly sequence adjustment. Finally, the proposed framework has proven to work when applied to a case study in the production machine manufacturing industry. To increase usability for engineers, the proposed framework has to be integrated into a Digital Twin. This would also simplify the integration of design change propagation in other areas such as supply chain and manufacturing. Through refinement during the application in other industries, the range of the proposed framework could be improved.